(Re-)Establishing familiarity: Resumption of occupations by older adults with physical disabilities. (19th September 2019) - Bontje, Peter; Alsaker, Sissel; Asaba, Eric; Kottorp, Anders; Josephsson, Staffan
Abstract: Background: There is a need for in-depth understanding of how elderly persons resume their occupations while recovering from physical disabilities in their home and community. The aim of this study was to explore and understand how engaging in occupations unfolded over time for some older persons with physical disabilities in Japan. Materials and methods: In this narrative-in-action study four elderly participants were recruited following a mixed purposive and convenience sampling method. Data was gathered at two to three weeks' intervals over six months, with a follow-up visit at nine months. Qualitative interviews and participant-observations were analyzed using narrative analysis. Results: This study identified the central meaning of resuming occupations as reestablishing former and establishing new familiarity. Familiarity was expressed in three features, namely as repertoires of occupations fulfilling needs and meanings, as performing occupations according to expectation, and as a resource for dealing with problems of engaging in occupation. What was experienced as familiar could be adjusted to accommodate ones changing needs or situation. Conclusion and significance: (Re-)establishing familiarity is a new concept representing transitions from an occupational perspective. Facilitating familiarity can assist older persons to experience health and well-being, even while transitioning after an illness or injury.